The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/138935
|View full text |Cite
|
Sign up to set email alerts
|

A Prevalence Study of Hearing Loss among Primary School Children in the South East of Iran

Abstract: Hearing impairment substantially affects child's ability to normally acquire the spoken language. Such negative effects create problems for the child not only in terms of communication but also in terms of achievement in school as well as social and emotional growth. The aim of this research is to study the prevalence of hearing disorders and its relationship to age and gender among primary school students of Zahedan, Iran. In this cross-sectional and descriptive analytical study, 1500 students from elementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
6
12
1
Order By: Relevance
“…In the present study, the most observed alteration in the meatoscopy was excessive cerumen, which is reported in literature as one of the most frequent causes of alterations in preschool and school-age children 1 . Recent studies have found that the presence of excessive cerumen in the EAC was the most common alteration found in students [20][21][22] , which complies with the results in this study. However, in other researches 10,11,23,24 , there the prevalence of excessive cerumen was a higher than in this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the most observed alteration in the meatoscopy was excessive cerumen, which is reported in literature as one of the most frequent causes of alterations in preschool and school-age children 1 . Recent studies have found that the presence of excessive cerumen in the EAC was the most common alteration found in students [20][21][22] , which complies with the results in this study. However, in other researches 10,11,23,24 , there the prevalence of excessive cerumen was a higher than in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The tympanometry is a quick and objective test designed to evaluate the functional integrity of the tympanic-ossicular system 7,36 , and that has been broadly used in hearing screening programs for precisely identifying conductive alterations. Like in this study, other authors have also observed the predominance of type A curves 37,38 , followed by type C, when performing the tympanometry in the school-age hearing screening 2,7,22,27 .The occurrence of 26.5% of types B, C, As and Ad tympanometric curves in this study's population, which may be related to middle ear and/or auditory tube alterations, infers that the findings were compatible with Therefore, the regular hearing screening of children during their school years would guarantee that they were affected by hearing loss or other preventable alterations. Information in this study demonstrate the importance of prioritizing the identification and early treatment of hearing impairments.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Wax was the most common diagnosis in many studies in our country and abroad. 9,10,11,12 It was followed by CSOM-TT and OME. There has been a lot of studies showing OME as a major cause of hearing loss in children.…”
Section: Discussionmentioning
confidence: 99%
“…A large study including more than 6000 children aged 6-19 years reported that 14.9% of them had some kind of hearing impairment [15], a study among 6581 grade 1 and grade 5 children in Australia found that the prevalence of slight/moderate bilateral sensorineural hearing loss was 0.88% [16] whereas a UK study suggested that 2.05% of children aged 9-16 years had permanent hearing impairment [17]. In developed countries, the prevalence of hearing impairments among primary school children ranged from 8.8% in Iran [18], 15% in Malasyia [8] but 2.4% in Zimbabwe [19].…”
Section: Introductionmentioning
confidence: 99%